Online game addiction and its impact on social-emotional development: A study of elementary school children in Sidoarjo - Firmansyah, Muhammad Fahrijal Arifudin; Faridah, Faridah; Astuti, Nur Muji; Sustrami, Dya (Svāsthya: Trends in General Medicine and Public Health, 2025)
The increasing popularity and accessibility of online games among schoolchildren, particularly through smartphones, has raised concerns about potential addiction, which may adversely affect their social-emotional development. The factors contributing to this issue include insufficient parental supervision and a lack of awareness. This study aimed to examine the relationship between online game addiction and social-emotional development in children. This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 171 respondents selected through a proportionate stratified random sampling method. The study utilized the Gaming Addiction Scale (GAS) and the Strengths and Difficulties Questionnaire (SDQ) to assess the levels of online game addiction and social-emotional development, respectively. Spearman's rho correlation test was applied for data analysis. Most respondents (52.6%) were categorized as having moderate online game addiction, whereas 91.2% exhibited abnormal social-emotional development. A statistically significant relationship was found between online game addiction and social-emotional development in school-age children, with a p-value of 0.001 and a moderate correlation coefficient of 0.310. Online game addiction significantly affects the social-emotional development of children. It is crucial to monitor children's game usage and its potential impacts. Prevention efforts should focus on educational interventions, support parents and schools.